A comparison and evaluation of innovative parabolic trough collector concepts for large-scale application. (February 2021) - Fredriksson, José; Eickhoff, Martin; Giese, Lutz; Herzog, Michael
Abstract: The present review defines the state of the art of parabolic trough collectors and identifies the concepts in the framework of innovation's requirements. These are the increase of operating temperatures and of the power plant's overall efficiency, as well as the cost reductions of the solar field by eliminating components and the reduction of parasitic power consumption (Pitz-Paal et al., 2007). The study investigates 34 collector concepts and classifies them according to their main structural features like mechanisms or materials. The categories include conventional collectors in Category A, collectors with alternative structure and sheet reflectors in Category B, with non-metallic materials like sandwich composite structures and concrete in Category C, with enclosed aperture in Category D and with fixed focus in Category E. For the technical-economic comparison, two conventional collectors vs. 14 innovations are analysed, following a design engineering method. The definition of a metric table defines the technical comparison criteria for those collectors suitable for thermo-oils or molten salts as heat transfer fluid. Results show that collectors operating with molten salts, instead of thermo-oil, have a significant techno-economic potential for utility scale application, for instance, the Molten Salt Trough, the UltimateTrough and the SkyFuelDSP (dispatchable solar power) as forerunners of their respective categories. Results show also that the inflatable Heliovis collector operating with thermo-oil has a relevant economic potential.